PLATELETS AMINO ACIDS PROFILE AND CARDIOMETABOLIC RISK FACTORS IN PATIENTS WITH CORONARY ARTERY DISEASE AND ATRIAL FIBRILLATION - Melnychuk, I.O. (World of Medicine and Biology, 2023)
The aim: to found out connections between platelets amino acids profile and cardiometabolic risk factors in coronary artery disease patients with atrial fibrillation. 300 patients were divided into 3 groups: first (I) – 149 patients with coronary artery disease and without arrhythmias, second (II) – 123 patients with coronary artery disease and atrial fibrillation paroxysm and 28 patients in control group. In II group in comparison with I group were checked (P